2024
DOI: 10.1177/20543581241227015
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors and Outcomes of Acute Kidney Injury in COVID-19 Patients in Kenya

Susan Cheruiyot,
Jacob Shabani,
Jasmit Shah
et al.

Abstract: Background: Corona Virus Disease 2019 (COVID-19), an infection caused by the SARS-CoV-2 virus, has been the largest global pandemic since the turn of the 21st century. With emerging research on this novel virus, studies from the African continent have been few. Corona Virus Disease 2019 has been shown to affect various organs including the lungs, gut, nervous system, and the kidneys. Acute kidney injury (AKI) is an independent risk factor for mortality and increases the health care burden for patients with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…65.0% (39 of 60) of patients were men, with the mean body mass index (BMI) of 26.00 ± 4.58 kg/m 2 . The median length of their hospital stay was 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days. Upon admission of these 60 patients of COVID-19, 6.7% (4 of 60) patients were classified as having a moderate condition; 80.0% (48 of 60) patients were presented with severe degree; and 13.3% (8 of 60) patients were critically ill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…65.0% (39 of 60) of patients were men, with the mean body mass index (BMI) of 26.00 ± 4.58 kg/m 2 . The median length of their hospital stay was 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days. Upon admission of these 60 patients of COVID-19, 6.7% (4 of 60) patients were classified as having a moderate condition; 80.0% (48 of 60) patients were presented with severe degree; and 13.3% (8 of 60) patients were critically ill.…”
Section: Resultsmentioning
confidence: 99%
“…This rate is comparable to studies with larger sample sizes conducted by Hirsch et al and Shchepalina et al, who found AKI incidence rates of 36.6% [11] and 38.0% [12], respectively. However, Cheruiyot et al found a lower AKI incidence rate of 21.6% [13]. Specifically, concerning patients in the ICU, Chan et al reported a higher occurrence rate of AKI, at 76%, for COVID-19-related AKI in ICU patients [14].…”
Section: Discussionmentioning
confidence: 98%